Education of Cyberbullying and Workshop of Pastoral Care For The Victims of Cyberbullying in Jemaat GPM Passo Anugerah: Edukasi Cyberbullying dan Workshop Pendampingan Pastoral bagi Remaja Korban Cyberbullying di Jemaat GPM Passo Anugerah - Ruimassa, Aleta Apriliana; Salenussa, Peter Boris; Nanuru, Ricardo Freedom (Universitas Lancang Kuning, 2024)
The objectives of this community service are to enhance: (1) knowledge about cyberbullying and its various forms, and (2) skills in providing pastoral care for adolescent victims, both from the perspective of the adolescents themselves and their caregivers at GPM Passo Anugerah Congregation, Ambon City. The methods used in this community service include: (1) multidisciplinary education on the issue of cyberbullying from psychological and pastoral perspectives, and (2) pastoral training and mentoring in the form of workshops for the participants, both for the adolescents and caregivers at GPM Passo Anugerah Congregation. The findings from this activity indicate that participants have a fair understanding of social media bullying, but are not yet trained in providing support to victims. The conclusion of this community service is that knowledge, when supported by adequate skills and collaboration among the various parties involved, will improve the ability of adolescents and caregivers to become more sensitive and skilled in handling cases of bullying.